Xanthogranulomatous pyelonephritis in a 47-day-old male infant: a case report - Jiang, Yeping; Chang, Menglin; Fu, Qian; Wang, Hui (Frontiers in Pediatrics, 2025)
BackgroundXanthogranulomatous pyelonephritis (XGP), a rare granulomatous renal disease linked to bacterial infection (e.g., Escherichia coli), presents challenges in pediatric diagnosis, especially in infants, due to overlap with neoplastic renal masses like Wilms tumor.Case SummaryA 47-day-old male infant with fever, elevated inflammatory markers (WBC 13.94 × 109/L, CRP 110.43 mg/L), and urinary leukocytes/hematuria showed a left renal mass (1.7 × 1.8 × 2.1 cm) on imaging. Biopsy revealed histiocytic-neutrophilic infiltration with focal necrosis, and metagenomic sequencing identified dominant E. coli. Antibiotic therapy (cefoperazone-sulbactam followed by cefdinir) induced regression (1.1 × 0.8 × 1.1 cm at 2 weeks). Elevated AFP (888.27 ng/ml) normalized, excluding malignancy.ConclusionThis case highlights XGP as a critical differential diagnosis for febrile infants with renal masses. Integration of histopathology, metagenomic sequencing, and prolonged follow-up confirms that focal XGP can be managed successfully with targeted antibiotics, avoiding nephrectomy.